War and state building in the Middle East - Schwarz, Rolf (Governance and international relations in the Middle East., 2011)
This book addresses the strengths and weaknesses of the authoritarian-regime governments commonly found in the Middle East, particularly among oil-rich countries. In this region, war has interacted with processes of state making in ways that fundamentally differ from the European experience. In short, unlike in Europe, wars do not make states in the Middle East; they destroy them.